Stilbene levels and antioxidant activity of Vranec and Merlot wines from Macedonia: effect of variety and enological practices - Kostadinović, Sanja; Wilkens, Andrea; Stefova, Marina; Ivanova, Violeta; Vojnoski, Borimir; Mirhosseini, Hamed; Winterhalter, Peter (Elsevier BV, 2012)
The content of the stilbenes trans-resveratrol and piceid as well as the antioxidant activity of Macedonian red wines from the two main grape varieties Vranec and Merlot have been evaluated. Тhe effects of time of maceration, type of yeast and the level of sulphur dioxide applied on stilbene content and antioxidant activity have been studied. The most important factor in winemaking technology is the maceration time since the highest concentrations of trans-resveratrol, piceid and highest antioxidant activity were found following 6 and 10 days of maceration. Concerning the yeast type, higher concentrations of trans-resveratrol and piceid have been obtained with French yeast "Levuline CHP" in comparison to Macedonian yeast "Vinalco". In contrast, the higher antioxidant activity of wines from both varieties of grapes was observed by application of Macedonian yeast "Vinalco".